Climate policy and wealth distribution - Nguyen Thang Dao (Osaka University, Institute of Social and Economic Research (ISER), 2021)
We set up a model with intergenerational bequest transfers and climate damage on the wealth of heterogeneous households. We show that, under credit market imperfections and depending on wealth distribution across households, a balanced budget climate policy may widen the wealth inequality gap between the rich and poor. Climate policy may create positive effects on the wealth of households, but these effects are asymmetric across households in terms of both magnitude and the transmission of gains from a climate policy within households. The gains of the poor from a climate policy are mainly transmitted into improving living standards and the investment in human capital due to the higher marginal return to education investment. By contrast, the gains of the rich from a climate policy are transmitted biasedly into physical capital accumulation and thereby enhance their monopolistic position in the production of intermediate inputs. We show that, for any climate policy, there exists a corresponding threshold of aggregate physical capital. When the aggregate physical capital of the economy exceeds this threshold, the corresponding climate policy may widen the intergenerational bequest transfers among heterogeneous households, thereby contributing to widening the wealth inequality gap between the rich and poor in the long run.
Keywords: D62; D63; O15; Q52; Q54; 330; Climate policy; balanced budget policy; credit market imperfections; intergenerationalbequest transfer; wealth inequality